Editorial - Nicolaiewsky, Clarissa de Arruda; Souza, Flávia Faissal de; Marafon, Giovanna; Calixto, Hector Renan da Silveira; Carijó, Maria Clara de Almeida; Souza, Marina Pereira de Castro e (Periferia, 2017)
DOI: 10.12957/periferia.2017.29418